Selectivity of resident and oesophageal fistulated steers grazing Arachis pintoi and Brachiaria dictyoneura in the Llanos of Colombia - Carulla, Juan E.; Lascano Aguilar, Carlos Eduardo; Ward, JK (1991)
Measurements were carried out at the Carimagua Research Station in the Llanos of Colombia, to (1) further characterise the nutritional value of A. pintoi (CIAT 17434) in association with B. dictyoneura cv. Llanero during the rainy (RS) and dry (DS) season, and (2) assess legume selectivity of resident and oesophageal fistulated steers grazing the pasture. Four paddocks (0.5 ha each) were rotationally grazed (7 days on/21 days rest) by 4 (group 1) or 3 (group 2) resident crossbred zebu steers in the RS and DS, respectively. In addition, 4 oesophageal fistulated steers were used to measure quality of ingested forage and legume selectivity during 5 periods of the year. The quality of the grass and legume on offer was determined in each of the 5 periods. Legume proportion in the diet of resident and fistulated steers was estimated using ?13C in the faeces and extrusa as well as by readings of extrusa by the microscope point technique. Crude protein (CP) and in vitro dry matter digestibility (IVDMD) of A. pintoi leaves on offer were 18.5% and 61.2% in the RS and 15.8% and 65.3% in the DS. Leaves of B. diclyoneura averaged 9.7 % CP and 5 8. 1 % lVDMD in the RS and 7. 1 % CP and 54% lVDMD in the DS. The lVDMD of the diet selected by oesophageal fistulated steers (56%) was similar throughout the year, whereas the CP varied between seasons, being higher in the RS (12.3 %) than in the DS (9.1%). Resident steers in group 1 and fistulated steers selected similar proportions of legume (42% and 47%, respectively). In contrast, resident steers in group 2 selected a lower (P < .001) proportion of legume (19%) than fistulated steers (34%). The results of this study confirm that A. pintoi is a high quality legume and that it is well consumed by previously adapted animals.